1995
DOI: 10.1073/pnas.92.22.10418
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the MSH3 gene preferentially lead to deletions within tracts of simple repetitive DNA in Saccharomyces cerevisiae.

Abstract: Eukaryotic genomes contain tracts of DNA in which a single base or a small number of bases are repeated (microsatellites). Mutations (2,3,6), whereas the msh3 mutation has only a 2-fold effect on the mutation rate (5); reversion rates of a frameshift mutation are elevated about 1000-fold by MSH2, MLH1, or PMS1 and about 10-fold by MSH3. Homologues to the yeast MSH3 gene exist in mice (7) and humans (8).Alterations in the length of simple repetitive DNA tracts in yeast are likely to reflect DNA polymerase sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 31 publications
12
120
1
Order By: Relevance
“…Furthermore, the frequency of insertion events approximately equaled the frequency of deletion events when insertionldeletion mispairs were repaired after transformation of wild-type S. cerevisiae cells, whereas there was a strong disparity in favor of deletion events among the fraction of insertionldeletion mispairs that appeared to be repaired in a pmsl mutant (Bishop and Kolodner 1986;Bishop et al 1987). A similar shift toward deletion events in mismatch repair mutants was seen when alterations in GT tract length resulting from replication errors were analyzed (Strand et al 1993(Strand et al , 1995. One of several possible explanations for these data is that there could be a separate, less-efficient repair pathway that selectively repairs insertionldeletion mispairs by deletion.…”
Section: Is There Another Eukaryotic General Mismatch Repair Pathway?mentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, the frequency of insertion events approximately equaled the frequency of deletion events when insertionldeletion mispairs were repaired after transformation of wild-type S. cerevisiae cells, whereas there was a strong disparity in favor of deletion events among the fraction of insertionldeletion mispairs that appeared to be repaired in a pmsl mutant (Bishop and Kolodner 1986;Bishop et al 1987). A similar shift toward deletion events in mismatch repair mutants was seen when alterations in GT tract length resulting from replication errors were analyzed (Strand et al 1993(Strand et al , 1995. One of several possible explanations for these data is that there could be a separate, less-efficient repair pathway that selectively repairs insertionldeletion mispairs by deletion.…”
Section: Is There Another Eukaryotic General Mismatch Repair Pathway?mentioning
confidence: 78%
“…Unlike either msh2 or msh6 mutants, msh3 mutants have little if any mutator phenotype in forward mutation and frameshift reversion assays and show increased dinucleotide repeat instability, albeit at lower levels, than that seen in msh2 mutants (New et al 1993;Alani et al 1994;Strand et al 1995;Marsischky et al 1996;). Strikingly, when double mutant strains were analyzed, msh3 and msh6 mutations showed a large synergistic effect on the rate of accumulation of mutations in frameshift reversion assays that measure the formation and repair of single-base insertion1 deletion mispairs (Marsischky et al 1996).…”
Section: Homologs Of the Bacterial Muts Proteinsmentioning
confidence: 99%
“…There are several observations in the literature, however, that have never been satisfactorily explained, and we suggest that these could reflect a strand asymmetry of MMR. Assays for dinucleotide repeat slippage, for example, found that 87% of events were due to a gain of repeat units in msh6 strains, whereas 85% of events were due to a loss in msh3 strains (41,42). Similarly, an examination of loss or gain of bases in mononucleotide repeats found a complex pattern that depended not only on the genetic background but also on whether there were Cs or Gs on the coding strand (43).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the central significance of microsatellite mutations to issues of genomic instability, forensic testing, and population genetic analyses, the rate of origin and spectrum of effects of such mutations are still poorly understood, with many estimates being derived from reporter constructs in yeast cultures (e.g., Henderson and Petes 1992;Strand et al 1995;Wierdl et al 1996;Sia et al 1997). Our long-term series of mutationaccumulation lines of C. elegans and D. pulex provide a useful platform for a more direct evaluation of the properties of microsatellite mutations in two key model organisms.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent reduction in the ability to repair a common form of DNA instability may be a consequence of the compromised ability of natural selection to maintain optimal features of genomic architecture in lineages of multicellular organisms with reduced effective population sizes (Lynch 2006(Lynch , 2007. For example, because mismatch repair (MMR) plays a central role in the elimination of post-replication slippage errors, specifically in microsatellite loci (Strand et al 1995;Wierdl et al 1996Wierdl et al , 1997Eshleman and Markowitz 1996;Boyer et al 2002;Yamadaet al 2002), a decline in the efficiency of MMR might be responsible in part for increased mutation rates in multicellular species.…”
Section: à4mentioning
confidence: 99%